Importance of the Wrist Extensor Muscle Training: Two Cases of Elbow Flexorplasty following Traumatic Brachial Plexus Injuries. (16th May 2018) - Kubota, Shigeki; Kubo, Tadashi; Kameda, Hiromi; Itoh, Yoshiyasu
Abstract : The modified Steindler procedure—a reconstructive surgery used to restore elbow flexion following upper brachial plexus injuries—involves shifting the origins of the muscle groups responsible for wrist flexion and forearm pronation originating from the medial epicondyle to the proximal direction to be used as flexors of the elbow. In the postoperative rehabilitation, we focused on strengthening not only the transferred muscle but also the wrist extensor muscles as antagonist muscles. After reconstruction surgery for elbow flexion via the modified Steindler procedure for traumatic brachial plexus injury, we performed long-term rehabilitation to strengthen the antagonist muscles. As a result, in two cases, excellent elbow flexion strength and gripping strength were achieved, confirming the importance of the antagonist muscles.